2012
DOI: 10.1016/j.jsb.2011.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Insights from the architecture of the bacterial transcription apparatus

Abstract: We provide a portrait of the bacterial transcription apparatus in light of the data emerging from structural studies, sequence analysis and comparative genomics to bring out important but underappreciated features. We first describe the key structural highlights and evolutionary implications emerging from comparison of the cellular RNA polymerase subunits with the RNA-dependent RNA polymerase involved in RNAi in eukaryotes and their homologs from newly identified bacterial selfish elements. We describe some pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 165 publications
(285 reference statements)
2
80
1
Order By: Relevance
“…Evidence of retrotransposable elements has been reported in another early branch of the Apicomplexa, the gregarines (28), and there is evidence that apicomplexan genomes which lack mobile elements used to contain them (29,30), or contain inactive elements as is the case in the apicomplexan coccidian parasite Eimeria tenella (31). More recently, non-integrase-associated bacterial AP2 proteins with architectures similar to AP2 proteins found in plants and alveolates have been reported (32). These AP2 proteins are also predicted to function as novel, specific transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of retrotransposable elements has been reported in another early branch of the Apicomplexa, the gregarines (28), and there is evidence that apicomplexan genomes which lack mobile elements used to contain them (29,30), or contain inactive elements as is the case in the apicomplexan coccidian parasite Eimeria tenella (31). More recently, non-integrase-associated bacterial AP2 proteins with architectures similar to AP2 proteins found in plants and alveolates have been reported (32). These AP2 proteins are also predicted to function as novel, specific transcription factors.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the G-hydrophobic residue in the smallresidue triad could be observed in the HTH DNAbinding domain , located in the α4/α5 loop (G-349, F-350, S-351); comparable, to the canonical hydrophobic residues in α3 (L-334) and α5 (F-356) (Figure 1-c). DNA binding motifs, from the HTH domain, were organized to facilitate DNAprotein interface binding to α3 residues (recognition helix) and the presence of hydrophobic residues in α1 and α3, stabilizing the domain (Iyer & Aravind 2012). It was also confirmed that these domains presented a tetra-helicoidal conformation, characterized by an additional C-terminal helix .…”
Section: Discussionmentioning
confidence: 80%
“…For DDRPs, the β subunit type DPBB was invaded by a SBHM that became the interaction surface for initiation and elongation factors (Fig. 3) required for use of a DNA template 4 , 6 . In this way, DDRPs evolved from RDRPs, prior to LUCA.…”
Section: The Old Testamentmentioning
confidence: 99%
“…Eubacteria, by contrast, because their gene regulatory networks are focused on the DNA interactome (Fig. 8B) 6 and mostly lack additional dimensions, have much simpler signal transduction mechanisms. The surprising similarities comparing the eukaryotic RNAP II transcription cycle and the eukaryotic cell cycle indicate that these processes are co-evolved 32 .…”
Section: The New Testament Of Eukaryotic Gene Regulatory Networkmentioning
confidence: 99%